(untitled) (Journal of Economic Research & Business Administration, 2016)
Development of transport infrastructure an important area of social and economic progress, to improve production efficiency. From the activity of this sector depend on the pace and level of development of society. At the same time the successful solution of many problems is determined by the effective management of transport complex. Currently, the development of transport infrastructure has a greater influence on the processes taking place in Kazakhstan. The leading role in the transport of the population of the republic and ensure the functioning of the economy belongs to the rail. Identifying features of the formation and development of railway transport in Kazakhstan is scientific and practical significance. The article deals with the role, value and classification of assets in rail transport. The peculiarities of analytical accounting and registration of primary documents of movement of fixed assets.